A KCNB1 gain of function variant causes developmental delay and speech apraxia but not seizures - Veale, Emma L.; Golluscio, Alessia; Grand, Katheryn; Graham, John M.; Mathie, Alistair (Frontiers in Pharmacology, 2022)
Objective: Numerous pathogenic variants in KCNB1, which encodes the voltage-gated potassium channel, Kv2.1, are linked to developmental and epileptic encephalopathies and associated with loss-of-function, -regulation, and -expression of the channel. Here we describe a novel de novo variant (P17T) occurring in the Kv2.1 channel that is associated with a gain-of-function (GoF), with altered steady-state inactivation and reduced sensitivity to the selective toxin, guanxitoxin-1E and is clinically associated with neurodevelopmental disorders, without seizures. Methods: The autosomal dominant variant was identified using whole exome sequencing (WES). The functional effects of the KCNB1 variant on the encoded Kv2.1 channel were investigated using whole-cell patch-clamp recordings. Results: We identified a de novo missense variant in the coding region of the KCNB1 gene, c.49C>A which encodes a P17T mutation in the N-terminus of the voltage-gated, Kv2.1 potassium channel. Electrophysiological studies measuring the impact of the variant on the functional properties of the channel, identified a gain of current, rightward shifts in the steady-state inactivation curve and reduced sensitivity to the blocker, guanxitoxin-1E Interpretation: The clinical evaluation of this KCNB1 mutation describes a novel variant that is associated with global developmental delays, mild hypotonia and joint laxity, but without seizures. Most of the phenotypic features described are reported for other variants of the KCNB1 gene. However, the absence of early-onset epileptic disorders is a much less common occurrence. This lack of seizure activity may be because other variants reported have resulted in loss-of-function of the encoded Kv2.1 potassium channel, whereas this variant causes a GoF.